'A Shower of Hail to All Orchards': On the Consumerist Interpretation of National Socialism. Issue 2 (4th May 2017) - Landa, Ishay
ABSTRACT: This paper critically examines what may be described as 'the consumerist interpretation of National Socialism.' In the last two decades or so, proponents of this approach have mounted a strong challenge to older assumptions about material scarcity under the Nazi regime. They have claimed that Nazism had brought about significant material benefits to the masses, and that, at the very least, the wish to ameliorate the material lot of the common folk was one of its main impulses. These revisionist arguments, however, downplay the reservations and often outright enmity of the Nazis towards mass consumption. The consumerist approach neglects the fundamental, elitist and quasi-libidinal investment of the Nazi worldview in war, and its no-less visceral opposition to peace as a way of life, despised not least on account of its association with consumerism, the cowardly and hedonistic fixation, precisely, on welfare and higher standard of life. Nazi social policies, including the final plunge into war, it will be argued, were less the deeds of homo economicus, and more acts conducted in accordance with Nietzsche's dictum: 'I know of no better aim of life than that of perishing, animae magnae prodigus, in pursuit of the great and the impossible.'